Long-latency gamma modulation after median nerve stimulation delineates the central sulcus and contrasts the states of consciousness. (January 2023) - Asman, Priscella; Pellizzer, Giuseppe; Tummala, Sudhakar; Tasnim, Israt; Bastos, Dhiego; Bhavsar, Shreyas; Prabhu, Sujit; Ince, Nuri F.
Highlights: The median nerve induced SSEPs contain spectral features in the gamma range that can delineate the central sulcus. The SSEP's long latency gamma activity is focal to S1 in the awake state. The SSEP's long latency gamma activity is suppressed in the anesthetized state and enhanced in the awake state. Abstract: Objective: To evaluate the functional use of sub-band modulations in somatosensory evoked potentials (SSEPs) to discriminate between the primary somatosensory (S1) and motor (M1) areas and contrast the states of consciousness. Methods: During routine intraoperative cortical mapping, SSEPs were recorded with electrocorticography (ECoG) grids from the sensorimotor cortex of eight patients in the anesthetized and awake states. We conducted a time–frequency analysis on the SSEP trace to extract the spectral modulations in each state and visualize their spatial topography. Results: We observed late gamma modulation (60–250 Hz) in all subjects approximately 50 ms after stimulation onset, extending up to 250 ms in each state. The late gamma activity enhancement was predominant in S1 in the awake state, where it discriminated S1 from M1 at a higher accuracy (92 %) than in the anesthetized state (accuracy = 70 %). Conclusions: These results showed that sensorimotor mapping does not need to rely on only SSEP phase reversal. The long latency gamma modulation can serve as a biomarker for primary sensorimotor localization and monitor the level of consciousness in neurosurgical practice. Significance: While the intraoperative assessment of SSEP phase reversal with ECoG is widely employed to delineate the central sulcus, the median nerve stimulation-induced spatio-spectral patterns can distinctly localize it and distinguish between conscious states.